Pancasila Student Profile Values Based on Local Wisdom in Hindu Elementary School - Dewi, Ni Putu Candra Prastya; Mariamah; Sudarsini, Ni Nengah; Sutrisna, I Putu Edi; Dikta, Putu Gede Asnawa; Dananjaya, I Nyoman Hari Mukti (Universitas Pendidikan Ganesha, 2024)
The challenge faced in forming the character of the young generation is the increase in juvenile delinquency triggered by the lack of attention and guidance from parents and the environment. This study aimed at analysing the implementation of the Pancasila Student Profile values ​​based on local wisdom in Hindu elementary schools. This research was case study research analysing the principal and teachers at Saraswati Elementary School Singaraja as the subjects of the research. This school was chosen because it was the only Hindu elementary school in North Bali. The data collection method was carried out by observation, interviews, and documentation. The data analysis method in this study was the Miles and Huberman qualitative analysis model. The results of the study indicated that the values ​​of the Pancasila Student Profile based on local wisdom that had been implemented at Saraswati Singaraja elementary school were Faith, Devotion to God Almighty, and Noble Character. Those values were shown as the students were provided with learning materials of Hindu Religious Education and Character Education (8 lesson hours per week) as well as they were guided to have habit of eating meals together. The Global Diversity Value had been instilled through practical activities by making Ketipat and Canang Sari. The Mutual Cooperation Value had been implemented in waste sorting. The Independent Value was reflected when students work independently on tests or exams. The Critical Reasoning Value was instilled when students were asked to criticize problems in the surrounding environment in the Pancasila Education subject. The Creative Value had been instilled during the activity of making decorative pictures of important figures from attractively decorated plastic food wrappers.